Gamification to Transform English Language Learning: A Conceptual Review - Fitriani, Rani Ligar; Hartono, Rudi; Bahri, Seful (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The use of gamification in English Language Teaching (ELT) has been found to employ more effective methods to improve learner participation, drive, and educational results. This review examines the impact of gamification in ELT by reviewing and consolidating major theories and their relevant evidence. The application of Self-Determination Theory, Flow Theory, the Multiliteracies Framework, Transformative Learning Theory, and Bloom’s Digital Taxonomy provide insight on the impact of gamified features, including, but not limited to points, badges, narratives, and feedback, on the ELT learner’s engagement with the subject. A comprehensive review of 25 selected articles published from 2014 to 2024 has shown that gamification has a desirable impact on learner’s motivation, autonomy, and participation within varying degrees of language skills. Furthermore, gamified approaches to instruction enhance the development of vocabulary and speaking skills, and learner perseverance. However, the review also identifies some issues, including the lack of effective implementation frameworks, inadequate professional development opportunities, and an excessive focus on badge and points systems that reward learners for competing with each other rather than collaborating. The results indicate that a well-designed gamified ELT course based on sound pedagogical theories increases learner engagement and active participation in learning. This study has considerable value for language educators and curriculum developers, in addition to stressing the need for more studies aimed at the effective use of gamification in language learning.